2016
DOI: 10.1007/s41061-016-0080-9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Prospect of Non-aqueous Non-alkali (NANA) Metal–Air Batteries

Abstract: Non-aqueous non-alkali (NANA) metal-air battery technologies promise to provide electrochemical energy storage with the highest specific energy density. Metal-air battery technology is particularly advantageous being implemented in long-range electric vehicles. Up to now, almost all the efforts in the field are focused on Li-air cells, but other NANA metal-air battery technologies emerge. The major concern, which the research community should be dealing with, is the limited and rather poor rechargeability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 128 publications
0
14
0
Order By: Relevance
“…Increased demand on new battery technologies for electrical energy storage devices, possessing very high-theoretical energy densities and being abundant in terms of resource availability motivate the ongoing research on metal-air batteries progressively [1][2][3][4][5][6][7][8][9]. Among the resource-efficient anode materials, the highest theoretical energy densities can be realized with aluminium and silicon; specific energies are 8091 Wh kg Al −1 and 8461 Wh kg Si −1 while energy densities are 21,845 Wh L Al −1 and 19,715 Wh L Si −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased demand on new battery technologies for electrical energy storage devices, possessing very high-theoretical energy densities and being abundant in terms of resource availability motivate the ongoing research on metal-air batteries progressively [1][2][3][4][5][6][7][8][9]. Among the resource-efficient anode materials, the highest theoretical energy densities can be realized with aluminium and silicon; specific energies are 8091 Wh kg Al −1 and 8461 Wh kg Si −1 while energy densities are 21,845 Wh L Al −1 and 19,715 Wh L Si −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] In this regard, various kinds of ionic-liquidbased electrolytes including 1-ethyl-3-methylimidazolium chloride, [13][14][15][16] 1-butyl-1-methylpyrrolidinium bis(tri-uoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium bis (triuoromethylsulfonyl)amide, and trihexyl tetradecyl phosphonium bis(triuoromethylsulfonyl)imide have been investigated as electrolytes. [17][18][19] Especially aluminium oxide or hydroxide has been successfully eliminated by applying 1-ethyl-3-methylimidazolium oligo-uoro-hydrogenate as an electrolyte, by replacing the aluminium oxide layer with an Al-O-F layer. Shvartsev et al exhibited that this newly built up layer restricts Al corrosion while enabling high rates of Al anodic dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Nevertheless, byproducts are still observed with the use of ionic liquid based electrolytes on the air cathode, which inhibit further electrochemical reactions. [13][14][15][16][17][18][19] On the other hand, non-oxide ceramic materials, e.g., nitride, carbide, oxynitride, and carbonitride, have been applied for use as cathodic materials for PEFCs (polymer electrolyte fuel cells) as well as Li-air and Zn-air batteries, due to their oxygen reduction reaction catalytic effect. 22,23 For example, Sampath et al had reported that air cathodes composed of titanium carbonitride (TiCN) nanostructures could exhibit excellent electrochemical performance for the oxygen reduction reaction in alkaline media for both primary and rechargeable zinc air batteries.…”
Section: Introductionmentioning
confidence: 99%
“…However, while there are several excellent reviews about other metal-air battery systems such as zinc-air- [44,[113][114][115] and lithium-air [36,40,81,116,117], as well as metal-air batteries in general [37,38,79,118], very few has been written about silicon-and iron-air batteries. To the best of the author's knowledge, only the review by Gelman et al is concerned with (non-aqueous) silicon-air batteries [50], while there is also only one recent minireview about iron-air batteries written by McKerracher et al [119]. Accordingly, in the present review, we will focus on aqueous silicon-and iron-air batteries.…”
Section: Systemmentioning
confidence: 97%
“…Present Al-air-and Li-O2 cells exhibit specific discharge capabilities of up to 1500 Wh/kgMe and more, but are only rechargeable for a few tens of cycles, yet [41,55,98,105]. Furthermore, in case of Si-air batteries, electrochemical rechargeability has not been shown yet, which is, however, no reason to discontinue the research on this type of battery [50,52]. Considering primary applications, silicon-based batteries from scrap material could be a decent option to replace primary Zn-air batteries in the future, given the excellently flat and long-lasting discharge characteristics of silicon in comparison to zinc.…”
Section: Electrochemical Performance Of Metal-air Batteriesmentioning
confidence: 99%